ENTREPRENEURSHIP, EDUCATION AND CREDIT: A GENERAL EQUILIBRIUM APPROACH - OYEGUN GBENGA; CHUKWUMA FRANCIS OGORCHUKWU (Research Parks Publishers, 2023)
This study explores the interconnected dynamics of entrepreneurship, education and credit within the framework of general equilibrium. Entrepreneurship plays a pivotal role in economic development and access to credit is crucial for fostering innovation and sustainable growth through a general equilibrium model, we analyze how investments in education impact entrepreneurial activities and access to credit, considering the feedback effects on overall economic equilibrium. The study delves into the nuanced interactions between educational policies entrepreneurial behavior, and credit market dynamics, providing insights into the broader implications for economic stability and prosperity. The findings contribute to the understanding of the complex relationships among entrepreneur, education, and credit within the context of a comprehensive general equilibrium framework.